ВОДА КАК ВАЖНЕЙШИЙ ПРИРОДНЫЙ РЕСУРC - У.Н. Раимжанова; Ш.Тураев (International Scientific and Current Research Conferences, 2023)
This article is devoted to the study of such issues as water security, which is a global condition for the life of mankind. Today, in some places there are territories that are unable to provide not only an abundance of clean water, but also the vital need for clean water. In the conditions of limited and scarce water resources in the Republic of Uzbekistan, the problem of water security is considered as an integral part of national security. Considering the aggravation of water problems in the world and the Central Asian region, as well as the special importance of water resources for the country.